2018
DOI: 10.1016/j.stemcr.2018.11.002
|View full text |Cite
|
Sign up to set email alerts
|

The MicroRNA-371 Family as Plasma Biomarkers for Monitoring Undifferentiated and Potentially Malignant Human Pluripotent Stem Cells in Teratoma Assays

Abstract: SummaryPredicting developmental potency and risk of posttransplantation tumor formation by human pluripotent stem cells (hPSCs) and their derivatives largely rely on classical histological analysis of teratomas. Here, we investigated whether an assay based on microRNAs (miRNA) in blood plasma is able to detect potentially malignant elements. Several hPSCs and human malignant germ cell tumor (hGCT) lines were investigated in vitro and in vivo after mouse xenografting. The multiple conventional hPSC lines genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 49 publications
4
24
0
Order By: Relevance
“…In order to extend the reach of our microRNA-identification model, we used a mouse xenograft model already described by us (which contains both benign and malignant teratoma samples as determined by teratoma assay); for details about the origin of animals and related information please refer to [50]. Briefly, the aforementioned (T)GCT cell lines and also human pluripotent stem cells (hPSCs) and induced pluripotent stem cells (IPS) were injected subcutaneously into immunodeficient mice and tumor xenografts grew until a maximum size of 2cm 3 (endpoint), after which they were collected for histological evaluation and microRNA isolation.…”
Section: Mouse Modelmentioning
confidence: 99%
“…In order to extend the reach of our microRNA-identification model, we used a mouse xenograft model already described by us (which contains both benign and malignant teratoma samples as determined by teratoma assay); for details about the origin of animals and related information please refer to [50]. Briefly, the aforementioned (T)GCT cell lines and also human pluripotent stem cells (hPSCs) and induced pluripotent stem cells (IPS) were injected subcutaneously into immunodeficient mice and tumor xenografts grew until a maximum size of 2cm 3 (endpoint), after which they were collected for histological evaluation and microRNA isolation.…”
Section: Mouse Modelmentioning
confidence: 99%
“…The reason for the non-expression of the miR by teratoma is probably related to the analogies of GCT biology and the human embryonal development [34,35]. While most of the GCT subtypes mimic early developmental stages of embryonal development and accordingly retain their biochemical characteristics including the microRNA profile of stem cells, the teratoma subtype represents a more advanced and more mature histological subtype that has lost all of the biochemical characteristics of stem cells particularly the typical expression of miR-371a-3p [36].…”
Section: Intracellular Localization Of Mir-371a-3p By Ishmentioning
confidence: 99%
“…Previous studies have shown that miRNAs can control the pathological process of II/R injury (Y. Hu et al, ; Z. Li et al, ; Y. Li, Wen, et al, ; Y. Li, Xu, et al, ). In addition, some miRNAs including miR‐375 and miR‐371 have been confirmed as the markers for clinical diagnosis and treatment of diseases (Piano et al, ; Salvatori et al, ). Circulating miRNA‐375 can be considered as a biomarker for active Kaposi's sarcoma in AIDS patients (Piano et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Circulating miRNA‐375 can be considered as a biomarker for active Kaposi's sarcoma in AIDS patients (Piano et al, ). The MiR‐371 family can be used as the plasma biomarkers for monitoring undifferentiated and potentially malignant human pluripotent stem cells (Salvatori et al, ). Besides, some groups have reported that miR‐29b‐3p plays important roles in cell apoptosis, inflammation, and oxidative stress (Jing et al, ; H. Wang et al, ; Xing et al, ; Zhang et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation